Crime and the Life Course in Another America: Collective Trajectory in Mexican Drug Cartel Dominated Communities. (23rd February 2023) - Chomczyński, Piotr A.; Clark, Timothy W.
Abstract: This article seeks to resolve inconsistencies with life course theory (LCT) that we observed in our ethnographic research on life in multiple highly impoverished communities in Mexico where residents are involved heavily with drug cartels. The theoretical areas examined are some of the core aspects of LCT: trajectory; the age-graded process; transitions; state dependence; effects from other institutions (religion, employment, family) on desistance; and, ultimately, why desistance and persistence differ in these Mexican communities compared with LCT expectations. Our results indicate that the weak State and drug trafficking organizations' dominance create structural conditions in which other institutions such as religion, family, and employment adapt using collectivism found in Mexican culture. Using the concept of collective trajectory (CT) to bridge the differences between our findings and LCT, we highlight how crime during the life course plays out differently in these more collectivistic communities.